Exploratory randomised trial of face-to-face and mobile phone counselling against usual care for tobacco cessation in Indian primary care: a randomised controlled trial protocol for project CERTAIN. Issue 1 (6th January 2022) - Panda, Rajmohan; Omar, Rumana; Hunter, Rachael; Prabhu, Rajath R; Mishra, Arti; Nazareth, Irwin
Abstract : Introduction: Despite widespread use of smokeless tobacco products by people within the Indian subcontinent, there is little awareness among Indians of its health hazards when compared with smoked tobacco. We hypothesise that mobile phone counselling will be feasible and effective for smokeless tobacco cessation intervention in India. This paper presents the protocol of the development and conduct of an exploratory trial before progression to a full randomised controlled trial. Methods and analysis: An exploratory randomised controlled trial will be conducted in urban primary health centres in the state of Odisha, India. A total of 250 smokeless tobacco users will be recruited to the study (125 in each arm). Participants in the intervention arm will receive routine care together with a face-to-face counselling intervention followed by advice and reminder mobile messages. The control arm will receive routine care, delivered by a primary care physician based on 'Ask' and 'Advice'. All participants will be followed up for 3 months from the first counselling session. The primary outcome of this trial is to assess the feasibility to carry out a full randomised controlled trial. Ethics and dissemination: Ethical approvals were obtained from the Institutional Ethics Committee of Public Health Foundation of India, Health Ministry's Screening Committee, Odisha State Ethics Board and also from University College London Research Ethics Committee, UK. The study findings will be published in a peer-reviewed scientific journal. Trial registration number: CTRI/2019/05/019484.